Aerobic capacity of professional soccer players before and after COVID-19 infection - Parpa, K.; Michaelides, M. (Scientific Reports, 2022)
This investigation assessed the effect of COVID-19 on the aerobic capacity of professional soccer players who have tested positive. Twenty-one division-1 elite soccer players (age 24.24±5.75 years, height 178.21±5.44 cm, weight 74.12±5.21 kg) participated in this study. This observational study compared the same players' aerobic capacity pre-, and 60-days post COVID-19 recovery. The statistical analysis demonstrated that the infected players had significantly lower VO2max values [t(20)=5.17, p<0.01, d=0.613 (medium effect)], and significantly lower VO2 values at RC [t(20)= 2.97, p<0.05, d= 0.39 (small effect)] after recovery. Furthermore, results indicated a significantly lower running time (RT) on the treadmill [t(20)=4.84, p<0.01, d=0.46 (small effect)] when compared to the results that were obtained before they got infected. In addition, velocity at VO2max (VVO2max) was significantly lower [t(20)=2.34, p<0.05, d=0.41 (small effect)] and the heart rate values at LT [t(20)= -2.79, p<0.01, d= 0.55 (medium effect)] and RC [t(20)= -3.72, p<0.01, d= 0.52 (medium effect)] were significantly higher post recovery. The aforementioned findings indicate that post COVID-19 soccer players may not reach full recovery at two months. Therefore, our results should alert practitioners and fitness coaches of the risk of longer-duration silent symptoms even in athletes that experience mild to moderate manifestations.